Quality by Design Driven Formulation Development, Optimization of Rosuvastatin Calcium Loaded Floating Microballoons: In Vitro and In Vivo Characterization - Kothamasu, Sasikanth; Swain, Suryakanta; Bhanoji Rao, Muddana Eswara; Jena, Bikash R. (Drug Delivery Letters, 2023)
Background : The prime intent of this study was to formulate, optimize and evaluate the floating microballoons of rosuvastatin calcium to extend the stomach or gastrointestinal residence time, dissolution rate, and bioavailability of the drug. Objective : Formulation development, statistical optimization, in vitro and in vivo characterization of floating microballoons of rosuvastatin calcium for cardiovascular diseases with improved dissolution rate, solubility, and bioavailability potential were the main objectives of this study. Methods: Rosuvastatin calcium-loaded floating microballoons were prepared by solvent evaporation technique and systematic optimization of such formulations by response surface methodology using Box-Behnken Design, with the selected independent variables like concentration of HPMC K4M (X1), K15M (X2), and K100M (X3) and dependent variables as mean particle size in µm (R1), % entrapment efficiency (R2), and % drug released at 12h (R3). For each of the studied response variables, the trial formulations were subsequently evaluated for in vitro floating lag time, drug content, total floating time, and drug content, and the data analysis through optimization was carried out by placing the experimental data with an appropriate mathematical model.Results : In vivo pharmacokinetics study parameters for the optimized batch showed a 4 to 5 folds elevation of peak plasma concentration (Cmax), the area under the curve (AUC) data, and reduction of time to reach peak concentration (Tmax) value compared to marketed product (p < 0.05). As per ICH guidelines, the stability study results show that floating microballoons remain stable for 6 months.Conclusion : Hence, the floating microballoons of rosuvastatin calcium are a valuable technique to improve the solubility, dissolution, and bioavailability of a poorly water-soluble drug, rosuvastatin calcium.
Keywords: entrapment efficiency